Recognition memory in developmental prosopagnosia: electrophysiological evidence for abnormal routes to face recognition - Burns, Edwin J.; Tree, Jeremy J.; Weidemann, Christoph T. (Frontiers in Human Neuroscience, 2014)
Dual process models of recognition memory propose two distinct routes for recognizing a face: recollection and familiarity. Recollection is characterized by the remembering of some contextual detail from a previous encounter with a face whereas familiarity is the feeling of finding a face familiar without any contextual details. The Remember/Know (R/K) paradigm is thought to index the relative contributions of recollection and familiarity to recognition performance. Despite researchers measuring face recognition deficits in developmental prosopagnosia (DP) through a variety of methods, none have considered the distinct contributions of recollection and familiarity to recognition performance. The present study examined recognition memory for faces in 8 individuals with DP and a group of controls using an R/K paradigm while recording electroencephalogram (EEG) data at scalp. Those with DP were found to produce fewer correct “remember” responses and more false alarms than controls. EEG results showed that posterior "remember" old/new effects were delayed and restricted to the right posterior area in those with DP in comparison to the controls. A posterior "know" old/new effect commonly associated with familiarity for faces was only present in the controls whereas individuals with DP exhibited a frontal "know" old/new effect commonly associated with words, objects and pictures. These results suggest that individuals with DP do not utilize normal face specific routes when making face recognition judgments but instead process faces using a pathway more commonly associated with objects.